A novel folic acid-conjugated TiO2–SiO2 photosensitizer for cancer targeting in photodynamic therapy - Feng, Xiaohui; Zhang, S.; Wu, H.; Lou, Xia (Elsevier BV, 2015)
In this paper, a novel folic acid-conjugated silica-coated titanium dioxide (TiO2–SiO2) photosensitizer was synthesized and characterized using various analytical instruments. The photosensitizer was further assessed with regards to its photoreactivity, cellular and hemocompatibility, cell internalization, and phototoxicity. Conjugating folic acid with TiO2–SiO2 has shown a significantly improved compatibility of the nanoparticles with the mouse fibroblast cells (L929) at 24 h. An improved compatibility with the human nasopharyngeal epidermoid cancer (KB) cells was also demonstrated, but to a slightly reduced degree. Enhanced cell internalization was well demonstrated in the TiO2–SiO2 folate nanoparticles. Upon exposure to UV light, TiO2–SiO2 folate nanoparticles maintained a high level photodynamic reactivity and yielded a 38–43% photo-killing of KB cells. The photo-killing effect increased with increasing dosage in the investigated concentration range of 50–100 μg ml−1.